Pengaruh Sosialisasi Perpajakan, Kualitas Pelayanan, dan Sanksi Perpajakan terhadap Kepatuhan WP dengan Kesadaran Wp Sebagai Variabel Intervening - Trixa Eka Wahyu Hidayat; Eko Budi Satoto; Ni Nyoman Putu Martini (Relasi : Jurnal Ekonomi, 2025)
This research aims to test and analyze the influence of tax socialization, service quality, and tax sanctions on taxpayer compliance with taxpayer awareness as an intervening variable. Type of quantitative research. The sample in this research was taken from existing population values ​​using the Slovin formula, the sample population used was 100 respondents, statistical tests used Warp PLS 6.0. The results of the research prove that Tax Socialization has a positive and significant effect on Taxpayer Awareness at KPP Pratama Jember, Service Quality has a positive and significant effect on Taxpayer Awareness at KPP Pratama Jember, Tax Sanctions Taxation has a positive and significant effect on Taxpayer Awareness at KPP Pratama Jember, Tax Socialization has a positive and significant effect on Taxpayer Compliance at KPP Pratama Jember, Service Quality has no positive and significant effect on Taxpayer Compliance at KPP Pratama Jember, Tax Sanctions have no positive and significant effect on Taxpayer Compliance at KPP Pratama Jember, Taxpayer Awareness has a positive and significant effect on Taxpayer Compliance at KPP Pratama Jember, Tax Socialization has a positive and significant effect on Taxpayer Compliance at KPP Pratama Jember with the variable Taxpayer Awareness as an intervening variable, Service Quality has no positive effect and significantly on Taxpayer Compliance at KPP Pratama Jember with the Taxpayer Awareness variable as the intervening variable, Tax Sanctions do not have a positive and significant effect on Taxpayer Compliance at KPP Pratama Jember with the Taxpayer Awareness variable as the intervening variable.